Find the value of cos 1 5 π cos 1 5 2 π cos 1 5 3 π cos 1 5 4 π cos 1 5 5 π cos 1 5 6 π cos 1 5 7 π
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
P = cos 1 5 π cos 1 5 2 π cos 1 5 3 π cos 1 5 4 π cos 1 5 5 π cos 1 5 6 π cos 1 5 7 π = cos 1 5 π cos 1 5 2 π cos 1 5 4 π cos 1 5 7 π × cos 1 5 3 π cos 1 5 6 π × cos 1 5 5 π = cos 1 5 π cos 1 5 2 π cos 1 5 4 π ( − cos 1 5 8 π ) × cos 5 π cos 5 2 π × cos 3 π = − sin 1 5 π sin 1 5 π cos 1 5 π cos 1 5 2 π cos 1 5 4 π cos 1 5 8 π × 2 1 ( cos 5 π + cos 5 3 π ) × 2 1 = − 2 sin 1 5 π sin 1 5 2 π cos 1 5 2 π cos 1 5 4 π cos 1 5 8 π × 2 1 ( 2 1 ) × 2 1 = − 4 sin 1 5 π sin 1 5 4 π cos 1 5 4 π cos 1 5 8 π × 8 1 = − 8 sin 1 5 π sin 1 5 8 π cos 1 5 8 π × 8 1 = − 1 6 sin 1 5 π sin 1 5 1 6 π × 8 1 = − 1 6 sin 1 5 π − sin 1 5 π × 8 1 = 1 2 8 1 Note that cos ( π − θ ) = − cos θ and cos A cos B = 2 1 ( cos ( A − B ) + cos ( A + B ) ) See proof: k = 0 ∑ n − 1 cos ( 2 n + 1 2 k + 1 π ) = 2 1
Reference: Proof for k = 0 ∑ n − 1 cos ( 2 n + 1 2 k + 1 π ) = 2 1
Problem Loading...
Note Loading...
Set Loading...
We will first calculate three values: cos 1 5 π cos 1 5 2 π cos 1 5 4 π cos 1 5 7 π cos 1 5 3 π cos 1 5 6 π cos 1 5 5 π The first value is given by:
cos 1 5 π cos 1 5 2 π cos 1 5 4 π cos 1 5 7 π
= 1 6 sin 1 5 π 1 6 cos 1 5 π sin 1 5 π cos 1 5 2 π cos 1 5 4 π cos 1 5 7 π = 1 6 sin 1 5 π 8 sin 1 5 2 π cos 1 5 2 π cos 1 5 4 π cos 1 5 7 π = 1 6 sin 1 5 π 4 sin 1 5 4 π cos 1 5 4 π cos 1 5 7 π = 1 6 sin 1 5 π 2 sin 1 5 8 π cos 1 5 7 π = 1 6 sin 1 5 π 2 sin 1 5 7 π cos 1 5 7 π = 1 6 sin 1 5 π sin 1 5 1 4 π = 1 6 sin 1 5 π sin 1 5 π = 1 6 1
The second value is given by: cos 1 5 3 π cos 1 5 6 π = 4 sin 1 5 3 π 4 sin 1 5 3 π cos 1 5 3 π cos 1 5 6 π = 4 sin 1 5 3 π 2 sin 1 5 6 π cos 1 5 6 π = 4 sin 1 5 3 π sin 1 5 1 2 π = 4 sin 1 5 3 π sin 1 5 3 π = 4 1
The third value is given by: cos 1 5 5 π = 2 1
Thus, the desired value:
cos 1 5 π cos 1 5 2 π cos 1 5 3 π cos 1 5 4 π cos 1 5 5 π cos 1 5 6 π cos 1 5 7 π = ( 1 6 1 ) ( 4 1 ) ( 2 1 ) = 1 2 8 1